The Effects of Departmental Demography on Turnover: The Case of a University - McCain, Bruce E.; O’Reilly, Charles A.; Pfeffer, Jeffrey (Academy of Management Journal, 1983)
The argument developed here is that turnover or exit behavior is, in part, a characteristic of the demography of the social system itself. University academic departments with a dominant cohort and those with substantial gaps among cohorts were found to be characterized by increased rates of voluntary retirements, resignations, and expired appointments.